The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41598-018-27081-1
|View full text |Cite
|
Sign up to set email alerts
|

The guanine nucleotide exchange factor Arhgef7/βPix promotes axon formation upstream of TC10

Abstract: The characteristic six layers of the mammalian neocortex develop sequentially as neurons are generated by neural progenitors and subsequently migrate past older neurons to their final position in the cortical plate. One of the earliest steps of neuronal differentiation is the formation of an axon. Small GTPases play essential roles during this process by regulating cytoskeletal dynamics and intracellular trafficking. While the function of GTPases has been studied extensively in cultured neurons and in vivo muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 77 publications
2
23
0
1
Order By: Relevance
“…αPix, encoded by ARHGEF6, has an 80% sequence homology with βPix protein and has been identified as a specific regulator of axonal and dendritic branching in hippocampal neurons [43]. The βPix/Ras/ ERK/PAK2 pathway is also involved in fibroblast growth factor-induced neurite outgrowth in PC12 cells [44], and βPix promotes axon formation as an upstream activator of TC10, which is closely related to Cdc42 [25]. Although previous studies have revealed the role of βPix in the extension of neuronal processes, those studies did not identify isoform-specific functions but mainly focused on the ubiquitous βPix-a isoform [26], in part due to the difficulty of isoformspecific genetic analysis.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…αPix, encoded by ARHGEF6, has an 80% sequence homology with βPix protein and has been identified as a specific regulator of axonal and dendritic branching in hippocampal neurons [43]. The βPix/Ras/ ERK/PAK2 pathway is also involved in fibroblast growth factor-induced neurite outgrowth in PC12 cells [44], and βPix promotes axon formation as an upstream activator of TC10, which is closely related to Cdc42 [25]. Although previous studies have revealed the role of βPix in the extension of neuronal processes, those studies did not identify isoform-specific functions but mainly focused on the ubiquitous βPix-a isoform [26], in part due to the difficulty of isoformspecific genetic analysis.…”
Section: Plos Onementioning
confidence: 99%
“…Rac1 and Cdc42 mediate different steps in neuronal morphogenesis, including neurite outgrowth and synapse formation, by regulating the reorganization of actin and microtubule [23]. Several studies have reported that βPix-a, a ubiquitous βPix isoform, regulates the formation of axons, spines, and synapses [24][25][26][27][28]. We have previously identified βPix-b and βPix-d, which are alternative spliced βPix isoforms that are specifically expressed in neurons [29,30] (Fig 1A).…”
mentioning
confidence: 99%
“…The relevance of Tuba in axon specification is reinforced by loss-and gain-of function approaches that highlight antagonistic effects over neuronal polarity acquisition. Consistently, loss-and gain-of-function for Cdc42 lead to similar results (Garvalov et al, 2007;Govek et al, 2018;Lopez Tobon et al, 2018;Schwamborn and Puschel, 2004). A truncated version of Tuba, called mTuba had no effect on neuronal polarity.…”
Section: Role Of Tuba In Neuronal Polarity Acquisitionmentioning
confidence: 53%
“…The information regarding TC10 upstream regulators is less known. Recently it was shown that, in hippocampal neurons, axonal formation is dependent on the activation of TC10 by Arhgef7, also known as βPix/Cool1 (Tobon et al, 2018), a GEF protein of the Dbl family that activates Cdc42 and Rac1 (Feng, Baird, & Cerione, 2004;Feng et al, 2006). Related to this evidence, it has been suggested that Reelin is able to activate Cdc42 and Rac1 via Arhgef6/αPix/Cool2, in the process of Golgi deployment in hippocampal neurons (Meseke, Rosenberger, et al, 2013), opening the possibility that Reelin effects over TC10 in hippocampal neurons as well as in DRG could be regulated with Arhgef7 and/or Arhgef6.…”
Section: Discussionmentioning
confidence: 99%
“…These molecular elements participate in the process of membrane expansion in axons, induced IGF-1 (Dupraz et al, 2009). Also, TC10 promotes neurite outgrowth through the exocytic fusion of Rab11-and L1containing vesicles (Fujita et al, 2013) and axon formation in hippocampal neurons (Tobon et al, 2018). Besides TC10 trafficking to the axonal growth cone, the local translation of the GTPase is also required for membrane expansion during axon outgrowth in PNS (Gracias, Shirkey-Son, & Hengst, 2014).…”
Section: Introductionmentioning
confidence: 99%